TECHNOLOGICAL PECULIARITIES OF THERMAL BARRIER COATINGS BASED ON ZIRCONIUM DIOXIDE - V. V. Okovity; O. G. Devoino; V. A. Okovity; V. M. Astashinsky (Наука и техника)
A technology for formation of thermal barrier coatings (TBC) based on zirconium dioxide has been developed in the paper. The paper investigates structures of phase composition and thermal stability of such developed coatings. Investigation results pertaining to formation of an oxide system ZrO2 – Y2O3, while using plasma spraying and subsequent high-energy processing, which allows to increase resistance of a thermal barrier coating to thermal cycling heat resistance of the coating at temperature of 1100 °C. This leads to longer protection of bottom layer against high-temperature exposure. The methodology is based on complex metallographic, X-ray diffraction and electron microscopy investigations of structural elements in composite plasma coatings of the ZrO2 – Y2O system. Resistance of plasma coatings (Мe – Cr – Al – Y/ZrO2 – Y2O3-type), used as TBC to protect gas turbine engine blades under conditions of frequent thermal cyclings is limited by cleavage of an outer ceramic layer. Structural and electron microprobe investigations have shown that as a result of thermal cycling an outer atmosphere due to porous structure of the ceramic coating layer, migrates to the surface of lower metal coating, causing its oxidation. As a result, the metal-ceramic Al2O3 layer is formed at a metal-ceramic interface and it changes a stress state of the coating that causes a reduction of protective properties. Thus, a high heat resistance of thermal barrier coatings depends on processes occurring at the interface between metal and ceramic coating layers. A laser impact on samples with TBC leads to changes in the structure of the oxide layer of ZrO2 – Y2O3. In this case its initial surface characterized by considerable relief is significantly flattened due to processing and the coating is fractured and it is separated in fragments. As the oxide coating has low thermal conductivity, and the time of laser exposure is about 10–3 sec, a heat flux does not have time to spread to a greater depth. As a result, the coating surface takes the form of solidified melt. The coating obtained from the powder of ZrO2 – 7 % Y2O3 in accordance with the developed technology can withstand heating – cooling cycles by 1.5-fold more than similar coatings being made previously. Thus the proposed method allows to increase the coating resistance to thermal cycling at temperatures of 1100 °C.